2023
DOI: 10.3390/toxics11040364
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Spraying of Gibberellins and Brassinolide on Cadmium Accumulation in Rice

Abstract: Cadmium (Cd) is one of the heavy metals that contaminate rice cultivation, and reducing Cd contamination in rice through agronomic measures is a hot research topic. In this study, foliar sprays of gibberellins (GA) and brassinolide (BR) were applied to rice under Cd stress in hydroponic and pot experiments. After foliar spraying of GR and BR, the biomass of rice plants grown in either hydroponics or soil culture was significantly higher or even exceeded that in the absence of Cd stress. In addition, photosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Research has shown that the addition of organic acid supplements could decrease Cd content in vacuoles, and, through enhancing the isolation of Cd by root vacuoles, thus contribute to maintaining plant growth and reducing Cd content [ 17 ]. The foliar application of inhibitors could reduce the transport of Cd from rice roots and stem bases to other parts by altering grain quality and lowering rice Cd content [ 41 ]. Additionally, when faced with heavy metal stress, CA may protect plant cell-structure integrity and stability by restoring ion balance within the plant.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the addition of organic acid supplements could decrease Cd content in vacuoles, and, through enhancing the isolation of Cd by root vacuoles, thus contribute to maintaining plant growth and reducing Cd content [ 17 ]. The foliar application of inhibitors could reduce the transport of Cd from rice roots and stem bases to other parts by altering grain quality and lowering rice Cd content [ 41 ]. Additionally, when faced with heavy metal stress, CA may protect plant cell-structure integrity and stability by restoring ion balance within the plant.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of Fe with Br28 and Br24 changed the Cd and As contents to a more reduced level in rice grains, suggesting that the use of Br28 and Br24 in combination with Fe is an effective way of reducing Cd and As contents in grains of rice [94]. Foliar spraying of brassinolide on rice plants under Cd stress resulted in increased root length and root surface area, and CAT, SOD, and POD activities were significantly improved, and the Cd content of rice was decreased by transforming Cd into immobile forms and fixing in the cell wall [95]. The application of Br24 decreased the rice growth but applying IP (iron plaque) in combination with Br24 increased its growth.…”
Section: Brassinosteroidsmentioning
confidence: 99%
“…Exogenous application of 24-epiBL increased the activity of antioxidant enzymes such as CAT to overcome the toxic effects caused by Pb of Brassica juncea seedlings (Santos NeriSoares et al 2020). Rice growing in Cd stress whereas application of BR resulted in growing CAT activity(Li et al 2023). Application of PBs caused a slight improvement in antioxidant activities in maize and soybean plants(De Vasconcelos et al 2009).…”
mentioning
confidence: 99%